Age-sex structure of population of Kharkov as the basis for its demographic capital - Сегіда, Катерина (Human Geography Journal, 2016)
The article defined the essence of the demographic capital. Age-sex structure of the population as the basis of the demographic capital was represented. Regularities of formation of sex-age structure of the population of the city Kharkiv was considered. The ratio of the population distribution by age and sex was determined. The main demographic indicators, demographic pressure and its distribution characteristics for the main groups of the population were calculated. Sex ratio of the population was analyzed. Age balancing was defined. Range of issues for further research of the population structure as the basis of the demographic capital city was delineated.